Understanding and optimizing the floating body retention in FDSOI UTBOX. (March 2016) - Aoulaiche, M.; Simoen, E.; Caillat, C.; Witters, L.; Bourdelle, K.K.; Nguyen, B.-Y.; Martino, J.; Claeys, C.; Fazan, P.; Jurczak, M.
Abstract: The floating body retention time is investigated on fully depleted SOI devices with UTBOX. The retention is occurring through the junctions and strongly assisted by defects in the junction space charge region during the holding state at a negative gate voltage. For standard devices with a gate overlap, the junction field is high and the dominant mechanism in this case is the generation by band-to-band tunneling. For optimized extensionless devices with lower junction field, the Shockley–Read–Hall generation enhanced by the field and Poole–Frenkel mechanism takes over the band-to-band tunneling. Therefore, reducing the concentration of Si impurities closer to the junctions is the key to approach an ideal retention time only due to band-to-band tunneling with the Si bandgap as the energy barrier for tunneling.